Foreign Policy of the Union State: Latin-Caribbean Direction of the Russia-Belarus Integration - V. A. Chmyreva (Евразийская интеграция: экономика, право, политика, 2024)
The research is aimed at studying the Union State foreign policy in the Latin-Caribbean direction in new geopolitical conditions and its role in the emerging architecture of world economy and geopolitics. The mechanism for implementing the Union State foreign policy has been determined. It is shown that the external contour of the Russia-Belarus integration is not the sum of foreign policies, but is being implemented within the framework of their legal framework: pursuing a coordinated foreign policy, the parties maintain a flexible approach and are not limited by the framework of the foreign policy institutions of the Union. The author presents basic areas of project cooperation between Russia, Belarus and the states of the Latin-Caribbean region establishing priorities of cooperation.Aim. To appraise the significance and potential of Latin-Caribbean direction in the Union State foreign policy in the current conditions of economic turbulence and geopolitical escalation.Tasks. To identify the main areas of cooperation, to analyze current trends and influencing factors, and to determine the prospects for interaction.Methods. A combination of general scientific theoretical and special methods is used. The method of comparative analysis and the logical method are of prime importance. When working with regulatory and legislative sources, the normative method is used.Results. The potential of cooperation between the Union State and the countries of Latin-Caribbean America has not been fully realized, however, an accelerated diversification of partnership between the countries is being practiced as well as an expansion of areas of interaction based on economic feasibility and political motivation.Conclusions. Under current conditions of global political and economic turbulence, the Latin-Caribbean direction of the Union’s foreign policy is an important part in building effective international cooperation and developing new trans-regional logistics routes.